Germany : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper on Germany focuses on current economic condition in the country. The build-up of Germany's current account surplus over the last decade does not lend itself to a single-factor explanation, as both global and domestic factors, as well as policy changes led to increased savings and lower investment. All sectors contributed to the build-up of the surplus. Although fiscal consolidation and higher household savings played a role, the corporate sector experienced a more pronounced shift. This paper provides a retrospective on these developments and explores whether the factors contributing to the surplus are likely to be reversed going forward. Although there are common global drivers for the non-financial corporations shift to a net lender position, several German-specific factors played a role, notably the labor market reforms in the 2000s, the business tax reforms, and the globalization of German firms' production chains. The households' saving-investment gap widened in the early 2000s as the pension reforms and growing income inequality boosted households' savings and residential investment declined by the end of the reunification construction boom.